A Review on Potential Biotechnological applications of Microalgae - Santhosh Sigamani, Dhandapani Ramamurthy, Hemalatha Natarajan (Journal of Applied Pharmaceutical Science, 2016)
Microalgae are microscopic photosynthetic organisms that are found in both marine and freshwater environments. Microalgae belong to the fastest growing photosynthetic organisms since their cell doubling time can be as little as a few hours. They are highly efficient biological approach for converting CO2 and nutrients to biomass. Eukaryotic microalgae and cyanobacteria have recently reemerged as promising organisms in the effort to develop sustainable options for production of food and fuel. Marine microalgae constitute a natural source of a variety of drugs for pharmaceutical, food and cosmetic applications—which encompass carotenoids, among others. The bioactive compounds derived from microalgae have anticancer, anti-inflammatory, antimicrobial, and antioxidant activities. The aim of this review is to discuss bioactive metabolites produced by microalgae for possible applications in the Biotechnological fields.
Keywords: Microalgae, metabolites, extraction, compound, toxins.